2021
DOI: 10.1177/0266242621989326
|View full text |Cite
|
Sign up to set email alerts
|

The geographical impact of the Covid-19 crisis on precautionary savings, firm survival and jobs: Evidence from the United Kingdom’s 100 largest towns and cities

Abstract: In this commentary, we trace the economic and spatial consequences of the Covid-19 pandemic in terms of potential business failure and the associated job losses across the 100 largest cities and towns in the United Kingdom (UK). The article draws on UK survey data of 1500 firms of different size classes examining levels of firm-level precautionary savings. On business failure risk, we find a clear and unequal impact on poorer northern and peripheral urban areas of the UK, indicative of weak levels of regional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 32 publications
(41 reference statements)
2
44
0
1
Order By: Relevance
“…Medium-(100-199 employees) and large-medium (200-249 employees) firms are on average 15% less likely to seek external loans than their smaller counterparts. This is consistent with earlier UK empirical evidence which identified a precautionary savings gap amongst these size classes of business which meant that they were in the most precarious liquidity position entering the Covid-19 crisis (Cowling, Brown and Rocha, 2002;Brown & Cowling, 2021). The evidence suggests that this weakened cash flow position led to an increase in the demand for loans during the Covid-19 crisis.…”
Section: Scarring From Previous Loan Rejectionsupporting
confidence: 89%
See 1 more Smart Citation
“…Medium-(100-199 employees) and large-medium (200-249 employees) firms are on average 15% less likely to seek external loans than their smaller counterparts. This is consistent with earlier UK empirical evidence which identified a precautionary savings gap amongst these size classes of business which meant that they were in the most precarious liquidity position entering the Covid-19 crisis (Cowling, Brown and Rocha, 2002;Brown & Cowling, 2021). The evidence suggests that this weakened cash flow position led to an increase in the demand for loans during the Covid-19 crisis.…”
Section: Scarring From Previous Loan Rejectionsupporting
confidence: 89%
“…The high general levels of non-borrowing amongst the small firm population suggest that in normal circumstances, the majority of small firms would selffinance their operational and investment needs. In the Covid-19 crisis, recent research has identified a lack of precautionary saving and retained earnings amongst micro and small businesses and this has directly affected their liquidity position during the series of business lockdowns that were imposed by government (Brown & Cowling, 2021;Cowling, Brown, et al, 2020;Cowling, Liu, et al, 2020;Cowling, Nadeem, et al, 2020). This lack of internal funds would imply that more firms would move to their second preference which is bank loans to shore up their cash position even in the face of declining opportunities for profitable investment.…”
Section: Pecking Order Hypothesismentioning
confidence: 99%
“…Yet, a gap remains with respect to findings on operational efficacy that may be leveraged by SMEs to improve performance or even thrive in challenging times. Thus, while Brown et al ( , 2021 and Cowling et al (2020) offer findings that policymakers may use to guide their efforts, we offer findings that businesses may use to form strategies. And while Manolova et al (2020) document strategies used by proactive women-owned businesses attempting to navigate today's volatile business environment, we quantitatively test a strategy to see whether it actually improved performance during COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…One category of companies that is rarely noticed when it comes to crisis management is small‐ and medium‐sized enterprises (SMEs; Doern, 2016 ; Eggers, 2020 ; Herbane, 2010 , 2013 ; Runyan, 2006 ). This is despite SMEs constituting 99% of all companies and generating 50%–60% of total economic production within the Organisation for Economic Co‐operation and Development (OECD, 2019 ), and their importance for regional economies and the welfare of nations (Björklund et al, 2020 ; Brown & Cowling, 2021 ; Doern, 2021 ; Kraus et al, 2020 ; Kuckertz et al, 2020 ; Thorgren & Williams, 2020 ). A possible explanation for the limited attention to SMEs in the crisis management literature might be the ambiguity about the efficacy of crisis management for SMEs.…”
Section: Introductionmentioning
confidence: 99%